MULTICULTURAL COMPETENCE OF PROSPECTIVE PRESCHOOL TEACHERS IN PREDOMINANTLY MUSLIM COUNTRY - Muhammad Solehuddin; Nandang Budiman (LPMPP Universitas Negeri Yogyakarta, 2019)
Prepared to teach young children in a multi-ethnic and religious society like in Indonesia, the prospective preschool teachers should have strong belief and practice in social justice and multiculturalism. However, this quality is not easily achievable by prospective teachers from ethnic and religious majority group, like Indonesian Muslim prospective preschool teachers who may have limited awareness and exposure to multicultural diversity. This study identified some existing multicultural competences of the participants before designing a training model to prepare prospective preschool teachers, to develop their multicultural competence. Data for this study were derived from the questionnaire and interview which reveal awareness, knowledge, and skill dimensions of multicultural competence. Findings show that the majority of the participants have a high level of multicultural awareness and indicate a difference in multicultural competence among different levels of students. Based on these findings and expert judgments, the study designs a training model to develop prospective preschool teachers’ multicultural competence which has the following sequence: systematic reflection, Socratic dialog, simulation, field practice, and reflection. The study also provides some recommendations on the inclusion of multicultural content into intracurricular and/or extracurricular activities as well as on testing and analyzing the effectiveness of the hypothetical training model resulted from this study.